Analysis of sex-specific injury patterns and risk factors in young high-level athletes - Frisch, A.; Seil, R.; Urhausen, A.; Croisier, J. L.; Lair, M. L.; Theisen, D. (Scandinavian Journal of Medicine & Science in Sports, 2009)
This study analyzed sex-specific injury patterns and risk factors in young athletes (n=256) from 12 sport disciplines practicing at the national or the international level in the Grand-Duchy of Luxembourg. Injury occurrence as a result of sport practice was analyzed retrospectively over the year 2006 using a standardized self-administered questionnaire. Overall incidence was not different between girls and boys (1.20 and 1.21 injuries/1000 athlete-hours, respectively), but in the context of team sport competition girls tended to be at a greater risk (rate ratio 2.05, P=0.053). Girls had a higher proportion of injuries in the ankle/foot region compared with boys (34.8% vs 16.8%). No sex-related differences were found regarding injury severity. Multivariate logistic regression (controlling for age and practice volume) revealed that girls' team sports were associated with a greater injury risk compared with individual sports [odds ratio (OR) of 4.76], while in boys this was observed for racket sports (OR=3.31). Furthermore, physical or emotional stress tended to be a specific risk factor in girls. There was a tendency for injury outside sports to be coupled to a higher injury risk in girls and boys. Consideration of sex-specific injury patterns and risk factors could be of importance for effective injury prevention.